PENGELOMPOKKAN DESA-DESA DI KABUPATEN GIANYAR BERDASARKAN FAKTOR-FAKTOR YANG MEMENGARUHI KEMISKINAN - Srinadi, I G A M; NILAKUSMAWATI, DESAK PUTU EKA; PRATIWI, LUH PUTU SAFITRI (PIRAMIDA, 2014)
This study aimstoclassifyrural/urban villages inGianyarregency, furtheranalyzethe characteristics(poverty profileand thefactors thataffectpoverty) that characterizeeach group ofvillages/urban village, thencomparedwiththe generalaverage valueof Gianyar regency.The data used in this study is secondary data sourced from Macroeconomic Data Publications In 2011, BadanPusatStatistik  (BPS) Gianyar district covers 64 villages and six villages (Village Gianyar, Village Abianbase, Beng Village, Village Bitera, Village Samplangan, and the Village of Ubud). The variables of study include: the percentage of poor households (Y) and the factors that affect poverty include: the percentage of health-care facilities (X1), the percentage of school facilities (X2), the percentage of the population working in the agricultural sector (X3), the percentage of the population who work in the formal sector (X4), the percentage of the working population in the informal sector (X5), the ratio of the number of television sets with the number of households (X6), the percentage of households using clean water (PDAM) (X7), the ratio of the population that has not complete primary school (X8), regular income village (X9), and the distance from the center of the village of Gianyar regency (X10). The methods and stages of analysis that used in this study are: (1) Describe the research variable is the variable percentage of the poor and the factors that influence it, and (2) Perform cluster analysis to classify rural/village based on the factors that affect poverty. The results showed that the percentage of poor households in 64 villages and 7 villages of Gianyar district shows that the percentage of poor households in the village of Batubulan lowest with 2.81 percent and the percentage of poor households occurred in the village was 73.18 percent Beresela . Group 1 consisting of village/village with a regular income that is high enough and the distance of the village/sub-district of the city center is quite low is a group of village / village with the average percentage of poor households most smaller than other groups in the amount of 25.67% lower than the average district worth 27,682%.
Keywords: poverty,poverty profile; thefactors of poverty; cluster analysis